Development of a community profile for alcohol and other drug use for the WDLDAG - Ilijovska, Ana; Howat, Peter; Maycock, Bruce; McManus, Alexandra (The Willetton and District Local Drug Action Group and Western Australian Centre for Health Promotion Research, Curtin University of Technology, 2005)
Rapid Assessment and Response (RAR) methodology was utilised for the development of a community profile of the Willetton and District area regarding the use of alcohol and other drugs and its associated problems. The process by which the community profile was developed was documented with the future aim of developing this process in the form of an RAR Guide that can be used by other community groups. This project was undertaken by the Willetton and District Local Drug Action Group (WDLDAG) in collaboration with the Western Australian Centre for Health Promotion Research (WACHPR) at Curtin University, Perth. The objectives of the project were: to establish the nature and extent of alcohol and other drug use and factors influencing this use; to establish the adverse consequences associated with alcohol and drug use and the factors influencing them; and to establish the resources available and current interventions within the community, relevant to drug and alcohol problems.Various sources were utilised to generate data for the community profile. Qualitative data was generated from 11 in-depth interviews and 3 focus group interviews with parents, students, teachers, school nurses, school counsellors, local police officers and other community members. Quantitative data was generated from the Australian School Students Alcohol and Drug Survey (ASSAD) and other local data. Data was successfully gathered and significant lessons were learnt regarding the investigation of a sensitive topic, working within a school setting and working with a community group. Overall, the alcohol and other drug use patterns in the Willetton and District area were in line with the average patterns of use throughout WA. The interviews provided suggestions for possible solutions to the identified alcohol and other drug use problems. It is intended that these suggestions will help inform strategies put that can be implemented by the WDLDAG and its members in response to the identified problems.